Patient, parent/carer, and health care professional experience of medication adherence in children and adolescents with asthma: a qualitative systematic review protocol. Issue 12 (29th December 2020) - Borg, Corey; Porritt, Kylie; Hotham, Elizabeth
ABSTRACT: Objective: This systematic review aims to identify and synthesize available qualitative evidence related to patient, parent/carer, and health care professional experiences of medication adherence in children and adolescents with asthma. Introduction: Poor medication adherence is a common cause of treatment failure in children with asthma. Research into promoting treatment adherence has found that the most effective interventions are complex. In a child with asthma, the child, the parents/carers, and the health care professional all have important roles in adhering to medication regimens. This review aims to explore the experiences of the patient, parent/carer, and health care professional in managing a child's asthma. Inclusion criteria: This review will consider children and adolescents between the ages of three and 19 years with asthma, as well as the parent/carer and health care professionals who care for a child with asthma. Qualitative studies exploring the experiences of adherence or nonadherence to asthma medication will be included. Methods: A three-stage search will be conducted and will include published and gray literature. Databases to be searched include CINAHL, Embase, PubMed, PyscINFO, Scopus, and Web of Science. Only studies published in English will be considered, with no date limitation. Identified studies will be screened for inclusion by two independent reviewers. Data will be extracted using a standardized tool, and reviewers will discuss any disagreement. Data synthesis will adhere to the meta-aggregative approach to categorize findings. The categories will be synthesized into a set of findings that can be applied as evidence-based practice.